2020
DOI: 10.1007/s11739-020-02539-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of the combination of echo-HRCT score as a tool to evaluate the presence of pulmonary hypertension in idiopathic pulmonary fibrosis

Abstract: Pulmonary hypertension (PH) is defined as an elevated mean pulmonary artery pressure at rest (mPAP ≥ 25 mmHg), evaluated by right heart catheterization (RHC). The aim of the present study was to evaluate HRCT findings in relation to transthoracic echocardiographic data to better characterize PH in IPF patients and to identify a non-invasive composite index with high predictive value for PH in these patients. 37 IPF patients were enrolled in this retrospective study. All patients underwent a complete assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…In human medicine, HRCT is commonly used in patients with lower airway disease (17), and in addition to specifying the cause of the disease, HRCT with computed tomographic angiography (CTA) can identify comorbidities with repercussions on prognosis such as PH (18). In humans, diameter of the pulmonary trunk (PT), pulmonary trunk-to-aorta ratio (PT/Ao), and right ventricle-to-left ventricle ratio (RV/LV) are measured alone or in combination to assess the presence of PH (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, HRCT is commonly used in patients with lower airway disease (17), and in addition to specifying the cause of the disease, HRCT with computed tomographic angiography (CTA) can identify comorbidities with repercussions on prognosis such as PH (18). In humans, diameter of the pulmonary trunk (PT), pulmonary trunk-to-aorta ratio (PT/Ao), and right ventricle-to-left ventricle ratio (RV/LV) are measured alone or in combination to assess the presence of PH (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…6 There are various etiological factors responsible for PAAs such as congenital heart disease, vasculitis (like Behcet's disease), infections (bacterial, tuberculosis, syphilis), malignancy, connective tissue disorders (Marfan or Ehlers-Danlos syndrome), pulmonary valve abnormalities, chronic pulmonary embolism, pulmonary hypertension, and idiopathic dilatation. 7 In our patient, we observed a quadricuspid pulmonary valve, a rare congenital abnormality, that is reported in 0.2% of 3861 donor hearts. 8,9 About two-thirds of these valves have a hypoplastic supernumerary cusp 10 that causes pulmonary regurgitation and eventually may lead to a PAA.…”
Section: Discussionmentioning
confidence: 52%
“…There are various etiological factors responsible for PAAs such as congenital heart disease, vasculitis (like Behcet's disease), infections (bacterial, tuberculosis, syphilis), malignancy, connective tissue disorders (Marfan or Ehlers–Danlos syndrome), pulmonary valve abnormalities, chronic pulmonary embolism, pulmonary hypertension, and idiopathic dilatation. 7…”
Section: Discussionmentioning
confidence: 99%
“…This may include the integration of multiple imaging modalities, 41 as studies have demonstrated that combining CT-based measures of pulmonary hypertension with echocardiography, for example, may be superior to either method in isolation. 42,43 In conclusion, in this study of individuals who underwent resection for early-stage lung adenocarcinoma, more severe pulmonary vascular pruning on CT was associated with greater small vessel pulmonary arterial remodeling on histology. These findings provide additional insight into the relationship between the pulmonary vessels' radiographic appearance and underlying histologic vasculopathy and suggest CT imaging may be a non-invasive indicator of pulmonary vascular disease.…”
Section: Discussionmentioning
confidence: 65%
“…This may include the integration of multiple imaging modalities, 41 as studies have demonstrated that combining CT-based measures of pulmonary hypertension with echocardiography, for example, may be superior to either method in isolation. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%